pH modulates the activity and synergism of the airway surface liquid antimicrobials β-defensin-3 and LL-37 - Abou Alaiwa, Mahmoud H. (Proc Natl Acad Sci U S A, 2014)
The pulmonary airways are continuously exposed to bacteria. As a first line of defense against infection, the airway surface liquid (ASL) contains a complex mixture of antimicrobial factors that kill inhaled and aspirated bacteria. The composition of ASL is critical for antimicrobial effectiveness. For example, in cystic fibrosis an abnormally acidic ASL inhibits antimicrobial activity. Here, we tested the effect of pH on the activity of an ASL defensin, human β-defensin-3 (hBD-3), and the cathelicidin-related peptide, LL-37. We found that reducing pH from 8.0 to 6.8 reduced the ability of both peptides to kill Staphylococcus aureus. An acidic pH also attenuated LL-37 killing of Pseudomonas aeruginosa. In addition, we discovered synergism between hBD-3 and LL-37 in killing S. aureus. LL-37 and lysozyme were also synergistic. Importantly, an acidic pH reduced the synergistic effects of combinations of ASL antibacterials. These results indicate that an acidic pH reduces the activity of individual ASL antimicrobials, impairs synergism between them, and thus may disrupt an important airway host defense mechanism.